The Heart and Brain in Counseling - Alghafri, Ali Salim Rashid (Journal of Educational and Psychological Sciences, 2022)
A psychological condition shocked by a sudden reality in her life, which is the discovery of a chronic disease, cried and fell asleep and lack of sleep anxiety and fear as a result, this situation was worried about the new experience; that made me deal with it by employing the characteristic of the experience of the heart and brain, and for a period of a year, this anxious condition began to accept the new pathological situation and then reduced fear and tension and became healthier more appropriate than the history of dealing with case.One of the roles of counseling is to provide the individual with academic advisement and psychological counseling and guidance and what that related to counseling in various psychological aspects and in classroom and extra-curricular courses to give the guided individual the knowledge, skill and emotional aspects of his / her condition. Since the counselor and counselee dominate between them in the counseling and guidance sessions the atmosphere of emotional sentiments and address the mind through the exchange of ideas according to the situation in the guidance process, the heart and the brain has a role in the process of the guidance and progress in the case of the counselee/advisee; Thus, the counselor’s knowledge for the important characteristics of the heart and brain that associated with the counseling and guidance process; helps him to improve the status of the counselee/advisee by employing these characteristics in himself and in the counselee/advisee during his counseling /guidance sessions according to the nature of his needs.
Keywords: Heart; Brain; Cognitive Neuroscience; Thinking; Emotion; Experience; Learning; Behavior; Process/Sessions of Counseling & Guidance